2018
DOI: 10.5588/ijtld.18.0043
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in childhood tuberculosis diagnosis at primary care clinics in Kampala, Uganda

Abstract: SUMMARY OBJECTIVE: To assess the quality of routine childhood tuberculosis (TB) evaluation in Kampala, Uganda. SETTING AND DESIGN: This was a cross-sectional study of children aged <15 years attending six government-run clinics from November 2015 to December 2016. Clinicians completed a standardized patient record form for all child visits. We assessed the following performance indicators of TB evaluation developed based on the Desk Guide of the International Union Against Tuberculosis and Lung Disease, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…At the end of the study period, TB screening was conducted for over 98% of all children that attended the IMNCI clinics. This is much higher than findings from Uganda, where 47.0% of those <15 years were screened for TB symptoms [25]. In the same Ugandan study, however, 15.0% of the screened children were identified as presumptive TB, which is much higher than the 0.6% in our study.…”
Section: Plos Onecontrasting
confidence: 90%
“…At the end of the study period, TB screening was conducted for over 98% of all children that attended the IMNCI clinics. This is much higher than findings from Uganda, where 47.0% of those <15 years were screened for TB symptoms [25]. In the same Ugandan study, however, 15.0% of the screened children were identified as presumptive TB, which is much higher than the 0.6% in our study.…”
Section: Plos Onecontrasting
confidence: 90%
“…This contributes to 55% of child TB cases not being reported to national programs [2] from high TB burden settings have consistently documented that health care workers feel uncomfortable about making a TB diagnosis in a child and that there are often delays in care [79]. For example, a cross-sectional study of six primary clinics in Kampala found that no children who met clinical criteria for TB had been started on anti-TB treatment [10]. While algorithms exist to identify children with TB based on clinical factors [11–13], a concern is that without microbiologic confirmation, misdiagnosis could result in poor outcomes or adverse events from anti-TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, TB is not systematically included in key policy frameworks, strategies, and operational tools to reduce child mortality, such as Integrated Management of Neonatal and Childhood Illnesses (IMNCI), or the management of acute malnutrition [44,45]. Providers of child and adolescent health services are not necessarily trained in basic TB prevention, diagnosis, and care; TB services are often managed and delivered separately by different providers [46]. Considerations around successful integration include: the selection of high yield service delivery points; human resource requirements (training as well as ongoing mentoring and supervision); referral pathways; and monitoring.…”
Section: Integrating Tb Care With Other Services For Children and Ado...mentioning
confidence: 99%